A relevância do valor da TI na avaliação de empresas que fazem uso intensivo de informação: um estudo sob a ótica dos profissionais de investimentos - Santos, Cássio Rogerio Celestino dos (2015)
In the process of evaluating companies, the definition of the fair value of an organization tends to represent in a balanced manner the economic potential of a given company, however, the assessment of companies is not an exact science, in search of true and unique values, since this procedure is surrounded by a series of subjective decision. Companies with high values of intangible assets and massive use of information technology, both at the operational level as in strategic, must somehow have the IT value represented in its valuation. In this context, this study aims to identify if the IT value is properly taken into account by investment professionals through the process of evaluating the companies that make intensive use of information. For this purpose, the influence of IT value is verified and its measurement model (through financial or non-financial indicators) in the evaluation process of these companies. Similarly, they examine the information provided by these companies to the market, whether they are sufficient for proper assessment procedure. The sample consists of 108 analysts and investment professionals active, in some way, in the process of business valuation. They answered 28 questions, and the statistical tool used for analysis and processing of data is the multiple linear regression. The results suggest that only the value of IT, identified by the variable "better relationship with customers," "development of new business plans" and "accuracy of information", have significant influence on the evaluation process of the companies that make intensive use of information. The survey also reveals that investment professionals consider the information provided by companies to the market insufficient for a proper assessment of the value of IT. The findings of this study help to confirm the relevance of the IT value in appreciation of these companies and to highlight the lack of appropriate information for a correct judgment of the IT value. Still, they collaborate with the presentation of a guidance map, which shows the main elements of the IT value considered in the process of business valuation, and finally, make suggestions of investment professionals regarding the disclosure of such information